KEBERADAAN FOLKLOR JAYAPRANA LAYONSARI DALAM MENINGKATKAN PARIWISATA DI BULELENG BARAT - Putu Agita Hary Devianti; Lestari, Made Novita Dwi (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2026)
Indonesia, as an archipelagic country, possesses abundant intangible cultural heritage, including folklore transmitted orally across generations. This study aims to analyse the existence of the Jayaprana Layonsari folklore and its contribution to enhancing cultural tourism in West Buleleng, Bali. A descriptive qualitative method was employed, with data collected through literature review, observation, interviews, and documentation at the Jayaprana Shrine in Teluk Terima. The findings reveal that the Jayaprana Layonsari folklore remains embedded in the collective memory of Balinese society and has undergone a transformation from oral tradition into a structured cultural tourism attraction. The narrative embodies local wisdom values such as loyalty (satya), sacrifice, moral integrity, social criticism toward abuse of power, and the concept of cosmic balance in Balinese Hinduism. The transformation of folklore into a tourism asset is manifested through the sacralization of space, interpretative storytelling, and cultural performances. Furthermore, this folklore contributes to strengthening destination identity, diversifying tourism products, empowering local communities, and supporting sustainable tourism development. Therefore, the Jayaprana Layonsari folklore functions not only as intangible cultural heritage but also as a strategic foundation for identity-based tourism development in West Buleleng.